Addressing a broken peer review process. Issue 3 (14th November 2016) - Hazen, Benjamin T.; Fawcett, Stanley E.; Ogden, Jeffrey A.; Autry, Chad W.; Richey, R. Glenn; Ellinger, Alexander E.
Abstract : Purpose: The purpose of this paper is to bring awareness to the logistics and supply chain management (L/SCM) community's broken review process. Design/methodology/approach: The authors diagnose some of the core problems that limit the L/SCM community from disseminating high-quality research in a timely manner. Findings: Problems attributable to authors, reviewers, and editors are described, and recommendations for each review process participant are provided. Originality/value: This editorial provides a call for further discussion and action in terms of how the community can improve the contribution to knowledge and society.